A humanização das condições de trabalho um estudo de caso na Alumínio Brasil LTDA - Oliveira, Samantha Lima de (2009)
To keep the organizations competitive, some business strategies are necessary aiming the increase in productivity and quality. Making employees in potential productive, developing them and encouraging them through their enhancement and understanding of the factors that influence their behavior and improvement of working conditions, according to some authors, ensure their engagement, commitment, and provide the best throughout the organization, promoting increased productivity and the efficient and effective achievement of corporate goals and objectives. Thus this work has as proposal to verify to what extent the assumptions of the humanization in work conditions are feasible in a current business reality. For this a case study was conducted Alumínio Brasil Ltda, a multinational company, to evaluate the stage of humanization in the company work conditions, and extracted a sample of 118 employees. A questionnaire containing 69 statements was used as a tool for data collection. It was perceived that the company is seeking a model of integrated management involving the environment, health, safety and quality in the processes, but confirmed the theoretical concept, allied with the application of the model analysis that guided the case study, it was noted structural limits imposed by the labor relations and evidence of the persistence of traditionalistic paradigms that make difficult the possibility in implementing the basic assumptions of humanization.